2020
DOI: 10.3390/microorganisms8050703
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactone Analogs Are Promising Antiviral Agents for the Treatment of Human Cytomegalovirus Infection

Abstract: The human cytomegalovirus (HCMV) is a widespread pathogen and is associated with severe diseases in immunocompromised individuals. Moreover, HCMV infection is the most frequent cause of congenital malformation in developed countries. Although nucleoside analogs have been successfully employed against HCMV, their use is hampered by the occurrence of serious side effects. There is thus an urgent clinical need for less toxic, but highly effective, antiviral drugs. Strigolactones (SLs) are a novel class of plant h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…These results are challenging in the field of antiviral research, since, besides inhibiting the late phases of the viral cycle, apoptosis has been shown to be a novel strategy that SLs rely on to exert their inhibitory role against viral replication. These results have been confirmed by in-silico molecular docking simulations, which predict a stable protein-ligand complex between the SL analogs and the modeled structure of the putative target IE1, which is employed by HCMV to escape apoptosis [ 145 ].…”
Section: Potential Of Sls In Human Healthmentioning
confidence: 81%
See 1 more Smart Citation
“…These results are challenging in the field of antiviral research, since, besides inhibiting the late phases of the viral cycle, apoptosis has been shown to be a novel strategy that SLs rely on to exert their inhibitory role against viral replication. These results have been confirmed by in-silico molecular docking simulations, which predict a stable protein-ligand complex between the SL analogs and the modeled structure of the putative target IE1, which is employed by HCMV to escape apoptosis [ 145 ].…”
Section: Potential Of Sls In Human Healthmentioning
confidence: 81%
“…Recently, our group has demonstrated, for the first time, the efficacy of a group of SL analogues as antivirals against members of the Herpesviridae family, in particular human cytomegalovirus (HCMV) [ 145 ]. HCMV is a widespread pathogen that can cause severe disease in immunocompromised individuals [ 146 ].…”
Section: Potential Of Sls In Human Healthmentioning
confidence: 99%
“…The study results provided a new way to fight immune dysfunction induced by HCMV infection [ 117 ]. In contrast, Biolatti et al demonstrated that strigolactones exert their antiviral properties by inducing the apoptosis of HCMV-infected cells [ 118 ]. Similarly, Mo et al revealed that treatment with chloroquine remarkably enhances the expression of cleaved caspase-3 in MCMV-infected retinal pigment epithelial cells and contributes to the apoptosis of infected cells [ 119 ].…”
Section: Novel Treatment Strategies For Hcmv-related Diseasesmentioning
confidence: 99%
“…The antiviral activity of a panel of synthetic SLS was tested against HMCV (Human Citomegalovirus) with the aim of identifying new druggable targets for anti‐HCMV therapy to be used in place of nucleoside therapy whose side effects are reported as very serious [42] . Compound 19 and 20 a (Figure 2) markedly inhibit the replication of different HCMV strains in vitro.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…In particular, the authors show that an SL‐dependent trigger for apoptosis of the infected cell may be a novel strategy against HCMV infection. Finally, in silico molecular docking simulations have been used to predict the interactions between the SL analogs and the modeled structure of the putative target IE1, which is known to inhibit apoptosis [42] . Antiviral therapy that is based on molecules exerting their effects by targeting cellular proteins instead of specific viral proteins is a promising solution, as they are not associated with drug resistance.…”
Section: Biomedical Applicationsmentioning
confidence: 99%